Haemocytometric profile of Nigerian patients with Covid-19 (2021)
The haemocytometric changes and possible interplay with duration of hospital stay, gender and age in Nigerians with COVID-19 were determined in this study. Routine haemocytometry was evaluated using a standard method and thereafter, neutrophil-lymphocyte ratio (NLR); a marker of inflammation was calculated. Neutrophil percentage, total white blood cell (WBC) count and NLR were significantly higher while lymphocyte percentage was significantly lower in patients with COVID-19 compared with the controls. In females with COVID-19, neutrophil percentage was significantly higher compared with the males. Considering length of hospital stay, monocyte percentage was significantly higher in patients who spent more than 10 days on admission compared with those with 10 or fewer days of admission. At discharge, the proportion of patients with monocyte percentage above the reference range was significantly lower compared with baseline. Also, monocyte percentage in COVID-19 patients had significant positive correlation with days on admission. Alteration in haemocytometry worsens with increasing age as percentages of monocyte and neutrophil, NLR and WBC count were significantly higher while the lymphocyte percentage was significantly lower in patients aged 40 years and above compared with younger patients. Also, age had significant positive correlation with percentages of monocyte and neutrophil, NLR and WBC count but a significant negative correlation with lymphocyte percentage. Haemocytometric changes and inflammation in COVID-19 patients increase with age. Also, monocyte count could be an indicator of longer hospital stay and its reduction might be an indicator of recovery from the disease.